2015
DOI: 10.4049/jimmunol.1500251
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to Pneumococcal Phosphorylcholine Modulates the Development of House Dust Mite Allergy during Adult Life

Abstract: Currently, approximately 20% of the global population suffers from an allergic disorder. Allergies and asthma occur at higher rates in developed and industrialized countries. It is clear that many human atopic diseases are initiated neonatally, and herald more severe IgE-mediated disorders, including allergic asthma, which is driven by the priming of TH2 effector T cells. The “hygiene hypothesis” attempts to link the increased excessively sanitary conditions early in life, to a default TH2 response and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 51 publications
(58 reference statements)
2
46
0
Order By: Relevance
“…Despite a robust antibody response, B6.Igh-C a mice immunized with MK7 as adults are not protected against allergic disease. These results are similar to our findings in the A. fumigatus fungal and HDM allergy models (15, 16), in which there was a striking age-related dependence for vaccination to induce effective protection against allergic reactions. A similar age-related effect has also been shown to be critical for the induction of iBALT (44).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite a robust antibody response, B6.Igh-C a mice immunized with MK7 as adults are not protected against allergic disease. These results are similar to our findings in the A. fumigatus fungal and HDM allergy models (15, 16), in which there was a striking age-related dependence for vaccination to induce effective protection against allergic reactions. A similar age-related effect has also been shown to be critical for the induction of iBALT (44).…”
Section: Discussionsupporting
confidence: 91%
“…Having demonstrated that environmental allergens, such as A. fumigatus and HDM, display antibody-reactive epitopes associated with certain bacteria (15, 16), we expanded our studies to analyze German cockroach ( Blattella germanica ) allergen. Cockroach particles were bound by purified monoclonal anti-α-1,3-glucan antibody, A16 (IgM,λ1) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the inhibitory effect of all these LPS on polyI:C were observed, but the implication of the pathogenic bacteria infection in allergy remains to be explored. Moreover, determining whether the inhibitory effect of LPS could be demonstrated with other bacterial components, such as peptidoglycan, teichoic acid, or phosphorylcholine in airway epithelial cells would be of interest (85). …”
Section: Discussionmentioning
confidence: 99%
“…They showed that injection of α1-3 dextran permanently altered the repertoire of carbohydrate-reactive B cells when given within a short window after birth, but not later (summarized in (62)). This antigen is known to activate B-1 cells (63), and is expressed on Aspergillus fumigatus as well as house dust mites, While immunization did not change anti- α1-3 dextran serum IgM levels, it expanded the repertoire of polysaccharide-specific B cells and protected the mice from increased airway reactivity and signs of TH2-mediated airway disease (64). In addition, recent studies suggested that a portion of mainly B-1 cell-derived maternal IgG3 antibodies binds to gut microbiota and is induced in a TLR-dependent manner (65).…”
Section: B-1 Cell Repertoire Selection and Maintenancementioning
confidence: 99%